Chinese Consumers and the Fashion Market (Springer Series in Fashion Business,, 2018)
This book provides essential insights into Chinese consumer behaviors in the growing and dynamic fashion market. With increasing consumer purchasing power, readily accessible global brands, heavy application of digital technology and social media, as well as growing awareness of environmental issues, the Chinese fashion industry faces great opportunities and challenges at the same time. The contributing authors provide observations and address issues related to middle class fashion consumption, sustainable apparel consumption, technology application in fashion retailing, and the select traditional and new industry segments in the context of China's recent and massive economic boom. As such, the book offers an invaluable reference guide for all academics and practitioners interested in the Chinese fashion market.